A comprehensive method for studying pore structure and seepage characteristics of coal mass based on 3D CT reconstruction and NMR. (1st December 2020) - Wang, Gang; Han, Dongyang; Qin, Xiangjie; Liu, Zhen; Liu, Jiangfeng
Highlights: A comprehensive method for studying pore structure and seepage characteristics. Multi-scale and visualization study of pore structure. The seepage phenomenon of water was studied by MRI. Abstract: The pore structure and seepage characteristics of coal are of great significance to the study of seepage effect of coal seam water injection. Because the current methods for comprehensively characterizing the pore structure and seepage effect of coal mass are imperfect, a multi-scale and visualization method for exploring coal structure and seepage effect is proposed. Through 3D CT reconstruction, Nuclear Magnetic Resonance (NMR) T2 spectrum and Magnetic Resonance Imaging (MRI), the pore size distribution, connectivity, and seepage characteristics of 4 coal samples are explored. The results show that the pore and fissure structures larger than 47.59 μm can be obtained through 3D reconstruction and the equivalent pore diameters (Deq ) of the 4 coal samples are mainly concentrated between 100 and 500 μm. Because the pore size distribution in 0–100 μm is supplemented through NMR, it is found that the pore size of each coal sample is mainly distributed between 0.01 and 0.1 μm. The 3D reconstructed pore structure is basically consistent with the water signal spectrum obtained by NMR in the water saturated state, and both methods show that samples Q-1 and Q-2 have good pore connectivity. In addition, it is indicated from the NMR seepage experiments that Q-1 and Q-2 have more seepage space made of large-scale pores and fissures, and thus better connectivity. Therefore, the seepage effect of water injection for coal mass with different structures can be reflected by combining CT and NMR methods to comprehensively characterize the pore structure at different scales, which eliminates the limitations of a single method.